Germanium-tin alloys: applications for optoelectronics in mid-infrared spectra - Fang Cizhe (Institue of Optics and Electronics, Chinese Academy of Sciences, 2018)
We summarize our work of the optoelectronic devices based on Germanium-tin (GeSn) alloys assisted with the Si3N4 liner stressor in mid-infrared (MIR) domains. The device characteristics are thoroughly analyzed by the strain distribution, band structure, and absorption characteristics. Numerical and analytical methods show that with optimal structural parameters, the device performance can be further improved and the wavelength application range can be extended to 2~5 μm in the mid-infrared spectra. It is demonstrated that this proposed strategy provides an effective technique for the strained-GeSn devices in future optical designs, which will be competitive for the optoelectronics applications in mid-infrared wavelength.